Spatial distribution of moisture and its relation with soil texture - Largaespada, Kenneth (2015)
At Esmeralda Farm (Guácimo, Limón Province, C.R.), planted to banana cv. Valery, the spatial distribution of soil humidity, and its relationship to some physical properties, were analyzed to determine the variability between the traditional method and use of TDR (Time Domain Reflectrometer) in the determination of soil humidity. Sampling was done in a quadricuar pattern, with 36 measurement points georeferenced by GPS at 2 soil depths. At each point the volumetric soil water was measured with 3 different TDR equipments (300, MP and MT), and compared with the traditional method of volumetric humidity (VHM) determination. Soil samples were also collected, for texture analysis; with these data, a geostatistical analysis was performed and the corresponding maps were drafted. The soils, of Loam to clayey Loam texture, showed variability between TDR and these determinations regarding the MHV, regardless of depth. On the surface, the highest correlation was found between the values of MHV and TDR-300 (r=0.69), followed by TDRMT (r=0.63) and finally the TDR-MP (r=0.59). At 30 to 60 cm depth, a positive but lower ratio values was found compared MHV with TRD- 300 and TDR-MP (0.47 and 0.38, respectively); no relationship was found with TDR-MT at this depth. In terms of field moisture map, a good representation between methods was found and it can be said that this method was effective in representing the spatial variation of soil moisture.